Fractal and geography: Fractal scanning in three different urban areas of Elazığ - Şıkoğlu, Emrah (My University, 2023)
The study of systems' ability to self-organize, internal structural balance, and space partitioning is the focus of a larger body of theories produced by mathematicians in the second half of the twenty-first century, which includes fractal theory and analysis. These theories focus on how the distribution of forms and urban functions within an urban agglomeration, the sequencing of the settlement system, the choice of a specific style of localization, or the evolution of urban sprawl is influenced by a region with inhomogeneous characteristics. The study's objective is to quantify how urban macro-forms reflect urban space. It is aimed to use fractal analysis, one of the methods that examine the structure of urban areas, as a measurement technique and to increase the recognition of this method in the community. When performing fractal analysis, the study area is generally evaluated holistically. Determining the place of the parts that make up this whole within the analysis is another aim of the study. The most basic method used in the study is the Fractal Analysis method. In order to make a relevant evaluation, Fractalyse 3.0 program was used. Two bases were created for the urban spots to be used in the program. While one of these bases is the parcels of Elazığ city center, the other one is buildings. In order to measure the parts of the whole mentioned as one of the aims of the study, three different regions of the city were identified and fractal analyzes were carried out separately for those regions. The study field covers all the central 42 neighborhoods where Elazığ city develops. According to the results obtained from the analysis, the Fractal dimension value of the city was 1.62. This value is a very interesting result as it is considered a transition criterion for cities to be fringed and compact. Accordingly, Elazığ city is a fringed city in the process of becoming compact. In the analysis of three different sections containing the parts that make up the whole, the fractal value of Doğukent neighborhood, located in the easternmost part of Elazığ city, was calculated as 1.70. This area, which has a compact structure, presents a positive response against the urban sprawl. The sample taken from the central part of the city, called the Center, showed a high value of 1.89 in fractal dimension. The fractal dimension value of the sample selected from the south of the city showed a high fringed result of 1.32.
Keywords: Elazığ; fractal; fractal dimension; fractal geography